Comparative Study of the Development of Mischocyttarus cassununga Von Ihering and Mischocyttarus cerberus styx Richards Colonies (Hymenoptera, Vespidae, Mischocyttarini) - Biagiotto, Renan Hohendorff; Shima, Sulene Noriko (EntomoBrasilis, 2017)
Abstract. Mischocyttarus is a genus of eusocial wasps belonging to the Polistinae subfamily. They build nests without envelopes, making it easier to take notes and follow the growth of the nest, allowing the observation of oviposition, development of the eggs, larvae and pupae, as well as the addition of new cells to the nest and hierarchical conflicts among adults. Mischocyttarus cerberus styx Richards and Mischocyttarus cassununga Von Ihering are representatives of a genus and tribe that occur only in the Americas and these species happen to occur in the municipality of Rio Claro (SP). The present work aimed to follow the development of colonies in order to develop a comparative approach of factors that interact with the colony cycle, to verify if the species show similar or diverse profiles from each other. Four locations were chosen to represent the sampling at the Universidade Estadual Paulista campus of Rio Claro, SP. Data collection ranged from April 2014 to April 2015. M. cerberus styx showed a more irregular profile of productivity along the four seasons, presenting in general the greatest values on summer and the lowest values on winter. M. cassununga, on the other hand, seemed to have a more stable rhythm of productivity, with less discrepancy between seasons, demonstrating a better performance concerning cold seasons, with the greatest productivity values on spring and the lowest values on fall. Both species showed a similar pattern of immature development with the shortest period corresponding to summer and the longest period corresponding to winter. Estudo comparativo do desenvolvimento colonial de Mischocyttarus cassununga Von Ihering e Mischocyttarus cerberus styx Richards (Hymenoptera, Vespidae, Mischocyttarini) Resumo. Mischocyttarus é um gênero de vespas eussociais pertencentes à subfamília Polistinae. Elas constroem ninhos sem envelopes, tornando-os mais facilmente observáveis e favorecendo o acompanhamento do crescimento do ninho, permitindo a observação de oviposição, desenvolvimento dos ovos, larvas e pupas, assim como a adição de novas células ao ninho e interações entre adultos. Mischocyttarus cerberus styx Richards (Hymenoptera, Vespidae, Mischocyttarini) e Mischocyttarus cassununga Von Ihering (Hymenoptera, Vespidae, Mischocyttarini) são representantes do gênero e tribo que ocorrem apenas nas américas, ocorrendo concomitantemente no município de Rio Claro (SP). O presente trabalho objetivou o acompanhamento do desenvolvimento colonial para elaborar uma abordagem comparativa de fatores que interagem com o ciclo colonial, a fim de verificar se as espécies apresentam perfil similar ou diverso entre si. Quatro locais foram escolhidos para representar a amostragem no campus da Universidade Estadual Paulista de Rio Claro, SP. O período de coleta de dados abrangeu abril de 2014 até abril de 2015, com os mapeamentos das colônias selecionadas na frequência de três vezes por semana, através do auxílio de escadas de diferentes alturas. M. cerberus apresentou um perfil mais irregular de produtividade conforme as estações, apresentando geralmente valores maiores no verão e os menores no inverno. M. cassununga por outro lado, apresentou um ritmo de produtividade mais estável, com menor discrepância entre as estações e melhor desempenho em períodos frios. Ambas as espécies demonstraram padrão similar no desenvolvimento de imaturos, sendo mais rápido no verão e mais longo no inverno.